Construção de consenso em negociações de acordos regionais - ARCs - Simões, Rosana Roa (2009)
The main subject of this study is the consensus analysis of negotiations of Regional Trade Agreements (RTAs). Generally speaking, delays and interruptions caused by controversies and impasses end up becoming strong efficiency problems which jeopardize the consensus building during any negotiation. As a justification, the target of this study is to identify processes to help obtain, efficiently, agreements in the RTAs negotiations. Its final objective was to search for theoretical tools and techniques to be applied in situations of stoppage in a sense of eliminating the difficulties or making them at least easier to deal with. Secondarily other theoretical points of view were considered with the intention of understanding how strategies and theoretical tools can contribute in each/or different scenario of the negotiation. Through the different ways of looking at it for the conduction of the negotiations, for evaluating the dimensions of the negotiations and in order to build up the consensus, the researcher was able to understand the perception and the interpretation of the subject in view. At last the conclusion was that the applicability of the chosen framework is positive in helping solve problems and controversies as well as building up the consensus during the negotiations.